Contact lens material, contact lens containing contact lens material and preparation method of contact lens material

By using a specific proportion of raw materials in contact lens materials, combined with biocompatible agents and anti-UV additives, the problem of insufficient oxygen permeability and biocompatibility of existing contact lens materials is solved, high moisture content, good oxygen permeability and effective ultraviolet protection are achieved, and wearing comfort and feasibility for long-term use are improved.

CN119708382APending Publication Date: 2025-03-28BEIJING NATURAL BEAUTY OPTICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411966663.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing contact lens materials have shortcomings in oxygen permeability and biocompatibility, which leads to uncomfortable wearing and inability to use for a long time.

Method used

Using a contact lens material containing a specific weight ratio of raw materials, including hydroxyethyl methacrylate, tetrahydrolanol, N-vinylpyrrolidone, etc., the moisture content, oxygen permeability and ultraviolet protection ability of the material are improved by the combination of biocompatible agents and anti-UV additives.

Benefits of technology

The high moisture content, good oxygen permeability and effective ultraviolet protection of contact lens materials are achieved, improving the wear comfort and feasibility of long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218522570000131
    Figure BDA0005218522570000131
Patent Text Reader

Abstract

The invention discloses a contact lens material, a contact lens containing the same and a preparation method of the contact lens material. The contact lens material is prepared from the following raw materials: hydroxyethyl methylacrylate, 2-methacryloyloxyethyl phosphorylcholine, azophenyl methacrylate, ethylene glycol dimethacrylate, 3-(methacryloyloxy) propyltrimethoxysilane, 2-acrylic acid 2-(4-benzoyl-3-hydroxyphenoxy) ethyl ester, isobornyl methacrylate, a solvent, a solvent, a solvent and a solvent. The component A is prepared from the following raw materials: tetrahydrolinalool, N-vinyl pyrrolidone, azodiisobutyronitrile, methacrylic acid and sodium hyaluronate; pDMS (Polydimethylsiloxane)-mono MA (Methacrylate) and IEM-PDMS (Induced The contact lens material provided by the invention has the advantages of good hydrophilicity, high water content and good biocompatibility, and the prepared contact lens has good oxygen permeability and water content, is comfortable to wear, also has ultraviolet protection and purple light and blue light filtering functions, and better protects eyes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of eyeglass materials, and more particularly to a contact lens material, a contact lens containing the same, and a preparation method thereof. Background Art

[0002] Contact lenses, also called contact lenses, are lenses worn on the cornea of ​​the eye to correct vision or protect the eyes. Contact lenses not only bring great improvements in appearance and convenience to patients with refractive errors such as myopia, hyperopia, and astigmatism, but also provide a wide field of vision and realistic vision. In addition, they also play a special role in controlling the development of myopia and astigmatism in adolescents and treating special eye diseases. According to different materials, contact lenses can be divided into hard contact lenses, soft contact lenses and gas permeable lenses. Among them, soft contact lenses were invented by Czechoslovak chemist Otto Wichterle in 1960. Because they are more comfortable to wear, they have become the most popular type of lenses today.

[0003] Soft contact lenses (SCL) are made of a hydrophilic synthetic polymer compound. The lenses are soft, elastic, and have good oxygen permeability. There is no obvious foreign body sensation when they are first used. According to the different materials, soft contact lenses can be divided into hydrogel contact lenses and silicone hydrogel contact lenses. Among them, the main material of hydrogel contact lenses is poly(2-hydroxyethyl methacrylate). Due to the low water content, one or more hydrophilic monomers such as N-vinylpyrrolidone (NVP), N,N-dimethylacrylamide (DMA), and methacrylic acid (MAA) are generally added to increase the water content. At the same time, the oxygen permeability of hydrogel lenses is low, and long-term wearing will cause dry eyes and sore eyes, affecting the comfort and experience of the wearer. The main materials of silicone hydrogel contact lenses are hydrophilic silicon-containing polymer materials and hydrophilic monomers, which can effectively improve the oxygen permeability. However, due to the hydrophobic surface of silicone hydrogel materials, they are less comfortable to wear. At the same time, silicone hydrogel contact lenses are prone to protein precipitation, causing lens pollution and cannot be worn for a long time. Therefore, they can only be made into short-term products with poor cost performance.

[0004] Therefore, how to provide a contact lens material with good hydrophilicity, high water content, good biocompatibility, high oxygen permeability, long-term wearability, and high cost performance and a contact lens containing the same is a problem that technicians in this field need to solve urgently. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a contact lens material, a contact lens containing the same and a preparation method thereof, which can achieve good water content, oxygen permeability and ultraviolet protection and ultraviolet and blue light filtering effects to solve the shortcomings of the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A contact lens material, characterized in that it comprises the following raw materials in parts by weight:

[0008] 30-35 parts of hydroxyethyl methacrylate, 8-13 parts of tetrahydrolinalool, 10 parts of N-vinyl pyrrolidone, 10 parts of PDMS-mono MA, 10 parts of IEM-PDMS, 5-10 parts of 2-methacryloyloxyethyl phosphorylcholine, 3-8 parts of isobornyl methacrylate, 0.7-1.0 parts of azophenyl methacrylate, 0.3-0.5 parts of ethylene glycol dimethacrylate, 0.25-1.0 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25-0.5 parts of 2-acrylic acid 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.2-0.4 parts of azobisisobutyronitrile, 0.2-0.4 parts of methacrylic acid and 0.1-0.2 parts of sodium hyaluronate.

[0009] Preferably, the above-mentioned contact lens material comprises the following raw materials in parts by weight:

[0010] 32-33 parts of hydroxyethyl methacrylate, 10-11 parts of tetrahydrolinalool, 10 parts of N-vinyl pyrrolidone, 10 parts of PDMS-mono MA, 10 parts of IEM-PDMS, 7-8 parts of 2-methacryloyloxyethyl phosphorylcholine, 5-6 parts of isobornyl methacrylate, 0.8-0.9 parts of azophenyl methacrylate, 0.3-0.4 parts of ethylene glycol dimethacrylate, 0.5-1.0 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25-0.4 parts of 2-acrylic acid 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.2-0.3 parts of azobisisobutyronitrile, 0.2-0.3 parts of methacrylic acid and 0.1-0.2 parts of sodium hyaluronate.

[0011] Preferably, the above-mentioned contact lens material comprises the following raw materials in parts by weight:

[0012] 32 parts of hydroxyethyl methacrylate, 10 parts of tetrahydrolinalool, 10 parts of N-vinyl pyrrolidone, 10 parts of PDMS-monoMA, 10 parts of IEM-PDMS, 8 parts of 2-methacryloyloxyethyl phosphorylcholine, 5 parts of isobornyl methacrylate, 0.8 parts of azophenyl methacrylate, 0.3 parts of ethylene glycol dimethacrylate, 0.5 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.4 parts of 2-acrylic acid 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.3 parts of azobisisobutyronitrile, 0.3 parts of methacrylic acid and 0.2 parts of sodium hyaluronate.

[0013] The beneficial effects of the present invention are:

[0014] 1. The contact lens material of the present invention contains a biocompatible agent 2-methacryloyloxyethyl phosphorylcholine, which has better hydrophilicity and biocompatibility, improves the water content of the contact lens material, makes the contact lens material have a higher water content, and increases the wearing comfort;

[0015] 2. The contact lens material of the present invention contains an anti-UV additive, 4-[(E)-phenyldiazenyl]phenyl-2-methacrylate, which can effectively prevent ultraviolet blue light with a wavelength of 400-500nm from causing macular degeneration of the eye lens, thereby reducing fundus lesions;

[0016] 3. The contact lens material of the present invention also contains an ultraviolet absorber, 2-acrylate 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, and the contact lens prepared thereby can effectively protect against photochemical damage caused by light radiation;

[0017] 4. 3-(Methacryloyloxy)propyltrimethoxysilane increases the oxygen permeability of contact lens materials, thereby increasing the oxygen permeability of contact lens materials and increasing the comfort of long-term wearing.

[0018] 5. The contact lens material of the present invention contains sodium hyaluronate, which can improve the lubricity of the contact lens, alleviate the dry feeling caused by the friction between the lens and the eyeball due to the dehydration of the lens caused by long-term wearing, and greatly improve the comfort of wearing the contact lens, especially the comfort of long-term wearing.

[0019] 6. Isobornyl methacrylate can mainly improve the flexibility of the lens.

[0020] 7. N-vinyl pyrrolidone: provides good air permeability, oxygen permeability and wettability for the lens, which can provide a more comfortable feeling for the wearer.

[0021] 8. PDMS-mono MA has excellent oxygen permeability

[0022] 9. IEM-PDMS: Improving the biocompatibility and oxygen permeability of contact lenses

[0023] The present invention also claims protection for a contact lens comprising the above contact lens material.

[0024] The present invention also claims protection for a method for preparing a contact lens, which specifically comprises the following steps:

[0025] (1) Weighing raw materials: Weighing the raw materials according to the weight of the above contact lens materials, mixing and stirring to obtain a contact lens raw material solution for later use;

[0026] (2) making a mold: making a convex mold whose bottom inner curvature is the same as the curvature of the contact lens, and a concave mold whose outer inner curvature is the same as the optical power of the contact lens;

[0027] (3) Pattern printing: printing the prepared color pattern on a convex mold to obtain a convex mold printed with the color pattern;

[0028] (4) Blank forming: first, inject the contact lens raw material liquid into the concave mold, then press the convex mold printed with a color pattern into the concave mold containing the contact lens raw material liquid, and dry and form it in a nitrogen oven to obtain a contact lens blank;

[0029] (5) demoulding: separating the dried male mold from the female mold to obtain a male mold containing the contact lens blank;

[0030] (6) Debonding: The contact lens blank is separated from the male mold to obtain the contact lens.

[0031] Furthermore, in the above step (1), the stirring speed is 100-200 r / min, preferably 150 r / min, and the time is 4-5 h.

[0032] Furthermore, in the above step (2), the specific steps of making the mold are:

[0033] A. Making the convex mold: Weigh an appropriate amount of polybutylene terephthalate (PBT) granules and put them into a dryer for drying. Then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the convex mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a convex mold with the same bottom inner curvature as the contact lens curvature.

[0034] B. Making the concave mold: Weigh an appropriate amount of PBT granules and put them into the dryer for drying, then take them out for standby use. After the injection molding machine barrel and the injection heating part reach the required temperature, add the dried PBT granules into the injection molding machine barrel, and install the iron mold for producing the concave mold on the injection molding machine as required. Then set the injection molding machine process parameters according to the process requirements and start molding to obtain a concave mold with the same external and internal curvature as the contact lens.

[0035] A further beneficial effect of adopting the above is that polybutylene terephthalate, also known as polytetramethylene terephthalate, is a polyester made by condensation polymerization of terephthalic acid and 1,4-butanediol. It is a milky white, translucent to opaque, semi-crystalline thermoplastic polyester with high heat resistance, can work for a long time at 140°C, has toughness, fatigue resistance, self-lubrication, low friction coefficient, and resistance to organic solvents. It can be used to manufacture electronic components that require high dimensional stability under long-term working conditions at high temperatures.

[0036] Furthermore, in the above step (3), the specific operation steps of pattern printing are: first, the designed contact lens pattern is engraved on the steel plate, and then printed on the convex mold by a pad printing machine, and finally the convex mold is placed in a 100-120°C blast oven for drying for 100-150 minutes, preferably 120 minutes, to obtain a convex mold printed with a color pattern.

[0037] Furthermore, in the above step (4), the oven is charged with 99.999% nitrogen, and the oven drying temperature is set to 110-120° C. for 40-60 min.

[0038] Furthermore, in the above step (5), the specific operation steps of demoulding are: the male mold that is pressed together after drying is separated from the female mold by a separator, and the contact lens blank is adhered to the male mold, and after separation, the male mold containing the contact lens blank is obtained.

[0039] Furthermore, in the above step (6), the specific operation steps of stripping are: separating the contact lens blank from the male mold by a separator, and the contact lens blank after separation is a contact lens with optical power.

[0040] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0041] The present invention discloses a contact lens material, a contact lens containing the same and a preparation method thereof. A biocompatible multi-coating layer composed of hydrophilic hydroxyethyl methacrylate and wettable 2-methacryloyloxyethyl phosphorylcholine is formed on the surface of a printed layer, so that the printed layer does not directly contact the eyes, and a moisture layer that does not dry is formed on the surface of the lens, thereby preventing the lens from dehydrating and providing a comfortable and wet wearing feeling for more than 12 hours. 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate is added to increase its thermal stability, so that it will not change due to heat during processing and can strongly absorb ultraviolet rays.

[0042] The contact lens material of the present invention has the advantages of good hydrophilicity, high water content and good biocompatibility. The contact lens prepared therefrom has good oxygen permeability and water content, is not only comfortable to wear, but also has the functions of ultraviolet protection and filtering out purple light and blue light, can be worn for a long period of time, and better protects the eyes. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] The contact lens material comprises the following raw materials by weight: 35 g of hydroxyethyl methacrylate, 13 g of tetrahydrolinalool, 10 g of N-vinyl pyrrolidone, 10 g of PDMS-mono MA, 10 g of IEM-PDMS, 5 g of 2-methacryloyloxyethyl phosphorylcholine, 8 g of isobornyl methacrylate, 1.0 g of azophenyl methacrylate, 0.5 g of ethylene glycol dimethacrylate, 1.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25 g of 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate, 0.2 g of azobisisobutyronitrile, 0.2 g of methacrylic acid and 0.1 g of sodium hyaluronate.

[0046] The method for preparing a contact lens is characterized in that it specifically comprises the following steps:

[0047] (1) Weighing raw materials: Weigh each raw material according to the weight of the above contact lens material, mix them, and stir them at a speed of 100 r / min for 4 hours to obtain a contact lens raw material solution for later use;

[0048] (2) Making mold:

[0049] A. Making the convex mold: Weigh an appropriate amount of polybutylene terephthalate (PBT) granules and put them into a dryer for drying. Then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the convex mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a convex mold with the same bottom inner curvature as the contact lens curvature.

[0050] B. Making the concave mold: Weigh an appropriate amount of PBT granules and put them into the dryer for drying, then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the concave mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a concave mold with the same external and internal curvature as the contact lens;

[0051] (3) Pattern printing: First, the designed contact lens pattern is engraved on the steel plate, and then printed on the convex mold by a pad printer. Finally, the convex mold is placed in a 100°C blast oven and dried for 100 min to obtain a convex mold printed with a color pattern.

[0052] (4) Blank molding: first, inject the contact lens raw material liquid into the concave mold, then press the convex mold printed with a color pattern into the concave mold containing the contact lens raw material liquid, and dry it in an oven filled with 99.999% nitrogen. The drying temperature is set to 110° C. and the drying time is 60 min to obtain the contact lens blank;

[0053] (5) demoulding: the male mold pressed together after drying is separated from the female mold by a separator, and the contact lens blank is adhered to the male mold. After separation, the male mold containing the contact lens blank is obtained;

[0054] (6) Delamination: The contact lens blank is separated from the male mold by a separator, and the contact lens blank after separation is a contact lens with optical power.

[0055] Example 2

[0056] The contact lens material comprises the following raw materials by weight: 30 g of hydroxyethyl methacrylate, 8 g of tetrahydrolinalool, 10 g of N-vinyl pyrrolidone, 10 g of PDMS-mono MA, 10 g of IEM-PDMS, 5 g of 2-methacryloyloxyethyl phosphorylcholine, 3 g of isobornyl methacrylate, 0.7 g of azophenyl methacrylate, 0.5 g of ethylene glycol dimethacrylate, 0.25 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25 g of 2-acrylate, 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.4 g of azobisisobutyronitrile, 0.2 g of methacrylic acid and 0.2 g of sodium hyaluronate.

[0057] The preparation method of contact lenses is the same as that of Example 1.

[0058] Example 3

[0059] The contact lens material comprises the following raw materials by weight: 33 g of hydroxyethyl methacrylate, 11 g of tetrahydrolinalool, 10 g of N-vinyl pyrrolidone, 10 g of PDMS-mono MA, 10 g of IEM-PDMS, 8 g of 2-methacryloyloxyethyl phosphorylcholine, 6 g of isobornyl methacrylate, 0.9 g of azophenyl methacrylate, 0.4 g of ethylene glycol dimethacrylate, 1.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.4 g of 2-acrylate 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.3 g of azobisisobutyronitrile, 0.3 g of methacrylic acid and 0.2 g of sodium hyaluronate.

[0060] The method for preparing a contact lens is characterized in that it specifically comprises the following steps:

[0061] (1) Weighing raw materials: Weigh each raw material according to the weight of the above contact lens material, mix them and stir them at a speed of 150 r / min for 5 hours to obtain a contact lens raw material solution for later use;

[0062] (2) Making mold:

[0063] A. Making the convex mold: Weigh an appropriate amount of polybutylene terephthalate (PBT) granules and put them into a dryer for drying. Then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the convex mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a convex mold with the same bottom inner curvature as the contact lens curvature.

[0064] B. Making the concave mold: Weigh an appropriate amount of PBT granules and put them into the dryer for drying, then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the concave mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a concave mold with the same external and internal curvature as the contact lens;

[0065] (3) Pattern printing: First, the designed contact lens pattern is engraved on the steel plate, and then printed on the convex mold by a pad printer. Finally, the convex mold is placed in a 110°C forced air oven and dried for 120 min to obtain a convex mold printed with a color pattern.

[0066] (4) Blank molding: first, inject the contact lens raw material liquid into the concave mold, then press the convex mold printed with a color pattern into the concave mold containing the contact lens raw material liquid, and dry it in an oven filled with 99.999% nitrogen. The drying temperature is set to 120° C. and the drying time is 40 min.

[0067] (5) demoulding: the male mold pressed together after drying is separated from the female mold by a separator, and the contact lens blank is adhered to the male mold. After separation, the male mold containing the contact lens blank is obtained;

[0068] (6) Delamination: The contact lens blank is separated from the male mold by a separator, and the contact lens blank after separation is a contact lens with optical power.

[0069] Example 4

[0070] The contact lens material comprises the following raw materials by weight: 32 g of hydroxyethyl methacrylate, 10 g of tetrahydrolinalool, 10 g of N-vinyl pyrrolidone, 10 g of PDMS-mono MA, 10 g of IEM-PDMS, 7 g of 2-methacryloyloxyethyl phosphorylcholine, 5 g of isobornyl methacrylate, 0.8 g of azophenyl methacrylate, 0.3 g of ethylene glycol dimethacrylate, 0.5 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25 g of 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate, 0.2 g of azobisisobutyronitrile, 0.2 g of methacrylic acid and 0.1 g of sodium hyaluronate.

[0071] The method for preparing a contact lens is characterized in that it specifically comprises the following steps:

[0072] (1) Weighing raw materials: Weigh each raw material according to the weight of the above contact lens material, mix them, and stir them at a speed of 200 r / min for 5 h to obtain a contact lens raw material solution for later use;

[0073] (2) Making mold:

[0074] A. Making the convex mold: Weigh an appropriate amount of polybutylene terephthalate (PBT) granules and put them into a dryer for drying. Then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the convex mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a convex mold with the same bottom inner curvature as the contact lens curvature.

[0075] B. Making the concave mold: Weigh an appropriate amount of PBT granules and put them into the dryer for drying, then take them out for standby use. After the material barrel of the injection molding machine and the injection heating part reach the required temperature, add the dried PBT granules into the material barrel of the injection molding machine, and install the iron mold for producing the concave mold on the injection molding machine as required. Then set the process parameters of the injection molding machine according to the process requirements and start molding to obtain a concave mold with the same external and internal curvature as the contact lens;

[0076] (3) Pattern printing: First, the designed contact lens pattern is engraved on the steel plate, and then printed on the convex mold by a pad printer. Finally, the convex mold is placed in a 120°C blast oven and dried for 150 min to obtain a convex mold printed with a color pattern.

[0077] (4) Blank molding: first, inject the contact lens raw material liquid into the concave mold, then press the convex mold printed with a color pattern into the concave mold containing the contact lens raw material liquid, and dry it in an oven filled with 99.999% nitrogen. The drying temperature is set to 115° C. and the drying time is 50 min.

[0078] (5) demoulding: the male mold pressed together after drying is separated from the female mold by a separator, and the contact lens blank is adhered to the male mold. After separation, the male mold containing the contact lens blank is obtained;

[0079] (6) Delamination: The contact lens blank is separated from the male mold by a separator, and the contact lens blank after separation is a contact lens with optical power.

[0080] Example 5

[0081] The contact lens material comprises the following raw materials by weight: 32 g of hydroxyethyl methacrylate, 10 g of tetrahydrolinalool, 10 g of N-vinyl pyrrolidone, 10 g of PDMS-mono MA, 10 g of IEM-PDMS, 8 g of 2-methacryloyloxyethyl phosphorylcholine, 5 g of isobornyl methacrylate, 0.8 g of azophenyl methacrylate, 0.3 g of ethylene glycol dimethacrylate, 0.5 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.4 g of 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate, 0.3 g of azobisisobutyronitrile, 0.3 g of methacrylic acid and 0.2 g of sodium hyaluronate.

[0082] The preparation method of contact lenses is the same as that of Example 4.

[0083] Comparative Example 1

[0084] The contact lens material differs from that of Example 3 only in that 80 g of hydroxyethyl methacrylate is not contained.

[0085] Comparative Example 2

[0086] The contact lens material is different from that of Example 3 only in that 80 g of hydroxyethyl methacrylate and 20 g of 2-methacryloyloxyethyl phosphorylcholine are not contained.

[0087] Comparative Example 3

[0088] The contact lens material is different from that of Example 3 only in that it does not contain 10 g of N-vinyl pyrrolidone.

[0089] Comparative Example 4

[0090] The contact lens material is different from that of Example 3 only in that it does not contain PDMS-mono MA10g and IEM-PDMS10g.

[0091] Comparative Example 5

[0092] The contact lens material differs from Example 3 only in that it does not contain sodium hyaluronate.

[0093] Performance Testing

[0094] The contact lenses prepared in Examples 1-5 and Comparative Examples 1-5 were respectively subjected to the following tests:

[0095] 1. Oxygen permeability coefficient (DK)

[0096] The GTG (gas to gas) analyzer (manufactured by REHDER DEVELOPMENT COMMY, USA) was used. The measurement time was 2 minutes and the measurement temperature was 35°C. The obtained values ​​were converted according to GB / T11417.7-2012 (Ophthalmic Optics, Contact Lenses Part 7, Physical and Chemical Properties Test Methods) to obtain the DK value (DK value means oxygen permeability coefficient value [(cm 2 / sec)·(mLO2 / mL·mmHg)], especially when the oxygen permeability coefficient is multiplied by 10 -11 The test results are shown in Table 1.

[0097] 2. Moisture content

[0098] After drying, contact lenses with a thickness of 0.5 mm were grouped into 10 pieces, and the dry weight of each group of contact lenses was measured. Then, the lenses were placed in a sample bottle filled with distilled water and immersed at 25° C. for 24 hours. The wet weight of each group of contact lenses was measured, and the average value was taken. The moisture content was calculated according to “moisture content (%) = {(wet weight - dry weight) / dry weight} × 100%”. The test is shown in Table 1.

[0099] 3. Optical index parameters (ultraviolet and blue light damage filtering rate)

[0100] The lens sample to be tested is placed on the test table of the TM-2 spectrometer (Topcon), and the range of relevant wavelength values ​​of absorption and transmission is set in the system. The transmittance of the ultraviolet band is quantitatively measured, and the collected data is calculated and compared. At the same time, the light beam is directly irradiated on the lens sample, and the energy of the light beam passing through the lens is measured. Then, the transmittance of this band (UV damage filtration rate) is calculated based on the transmitted energy. The test is shown in Table 1.

[0101] Table 1 Contact lens performance test results of Examples 1-5 and Comparative Examples 1-5

[0102] Test items DK value (GTG) Moisture content (%) UV damage filtration rate (%) Example 1 <![CDATA[17.0×10 -11 ]]> 51 98.4 Example 2 <![CDATA[16.9×10 -11 ]]> 49 99.3 Example 3 <![CDATA[17.1×10 -11 ]]> 50 99.5 Example 4 <![CDATA[16.7×10 -11 ]]> 49 99.1 Example 5 <![CDATA[16.5×10 -11 ]]> 48 98.6 Comparative Example 1 <![CDATA[9.0×10 -11 ]]> 47 89.3 Comparative Example 2 <![CDATA[7.6×10 -11 ]]> 41 91.6 Comparative Example 3 <![CDATA[7.2×10 -11 ]]> 46 92.4 Comparative Example 4 <![CDATA[5.8×10 -11 ]]> 35 88.4 Comparative Example 5 <![CDATA[7.1×10 -11 ]]> 37 89.8

[0103] As shown in Table 1, compared with Comparative Examples 1-5, the contact lenses prepared in Examples 1-5 of the present invention have higher DK values, moderate water contents, and higher UV damage filtration rates;

[0104] 4. Human trial evaluation

[0105] 150 myopic subjects, aged 10-50 years old, with random gender, were selected and divided into 10 groups, with 10 subjects in each group, and they wore the contact lenses prepared in Examples 1-5 and Comparative Examples 1-5 for 10 minutes, and then the myopic subjects' evaluation on the comfort effect of the contact lenses was statistically analyzed. The evaluation results are shown in Table 2.

[0106] Table 2 Evaluation results of contact lens comfort effects of Examples 1-5 and Comparative Examples 1-5

[0107]

[0108] It can be seen from Table 2 that, compared with comparative examples 1-5, the contact lenses prepared in embodiments 1-5 of the present invention have better comfort effects, and more than 90% of the people indicated that the comfort was good and there was no adverse reaction.

[0109] The above experiments show that the contact lens material of the present invention has the advantages of good hydrophilicity, high water content, good biocompatibility, and is comfortable to wear for a long time without drying out. The contact lenses prepared therefrom have good oxygen permeability and water content, are not only comfortable to wear, but also have ultraviolet protection and the filtering function of purple light and blue light, so as to better protect the eyes.

[0110] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0111] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A contact lens material, characterized in that: The invention comprises the following raw materials in parts by weight: 30-35 parts of hydroxyethyl methacrylate, 8-13 parts of tetrahydrolinalool, 10 parts of N-vinyl pyrrolidone, 10 parts of PDMS-monoMA, 10 parts of IEM-PDMS, 5-10 parts of 2-methacryloyloxyethyl phosphorylcholine, 3-8 parts of isobornyl methacrylate, 0.7-1.0 parts of azophenyl methacrylate, 0.3-0.5 parts of ethylene glycol dimethacrylate, 0.25-1.0 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25-0.5 parts of 2-acrylic acid 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.2-0.4 parts of azobisisobutyronitrile, 0.2-0.4 parts of methacrylic acid and 0.1-0.2 parts of sodium hyaluronate.

2. A contact lens material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 32-33 parts of hydroxyethyl methacrylate, 10-11 parts of tetrahydrolinalool, 10 parts of N-vinyl pyrrolidone, 10 parts of PDMS-monoMA, 10 parts of IEM-PDMS, 7-8 parts of 2-methacryloyloxyethyl phosphorylcholine, 5-6 parts of isobornyl methacrylate, 0.8-0.9 parts of azophenyl methacrylate, 0.3-0.4 parts of ethylene glycol dimethacrylate, 0.5-1.0 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.25-0.4 parts of 2-acrylic acid 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.2-0.3 parts of azobisisobutyronitrile, 0.2-0.3 parts of methacrylic acid and 0.1-0.2 parts of sodium hyaluronate.

3. A contact lens material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 32 parts of hydroxyethyl methacrylate, 10 parts of tetrahydrolinalool, 10 parts of N-vinyl pyrrolidone, 10 parts of PDMS-mono MA, 10 parts of IEM-PDMS, 8 parts of 2-methacryloyloxyethyl phosphorylcholine, 5 parts of isobornyl methacrylate, 0.8 parts of azophenyl methacrylate, 0.3 parts of ethylene glycol dimethacrylate, 0.5 parts of 3-(methacryloyloxy)propyltrimethoxysilane, 0.4 parts of 2-acrylate 2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, 0.3 parts of azobisisobutyronitrile, 0.3 parts of methacrylic acid and 0.2 parts of sodium hyaluronate.

4. A contact lens, characterized in that: The contact lens material comprises the contact lens material according to any one of claims 1 to 3.

5. A method for preparing a contact lens, characterized in that: The following steps are involved: (1) Weighing raw materials: weighing the raw materials according to the weight proportion of the contact lens material according to any one of claims 1 to 3, mixing and stirring to obtain a contact lens raw material solution for later use; (2) making a mold: making a convex mold whose bottom inner curvature is the same as the curvature of the contact lens, and a concave mold whose outer inner curvature is the same as the optical power of the contact lens; (3) Pattern printing: printing the prepared color pattern on a convex mold to obtain a convex mold printed with the color pattern; (4) Blank forming: first, inject the contact lens raw material liquid into the concave mold, then press the convex mold printed with a color pattern into the concave mold containing the contact lens raw material liquid, and dry and shape it in a nitrogen-filled oven to obtain a contact lens blank; (5) demoulding: separating the dried male mold from the female mold to obtain a male mold containing the contact lens blank; (6) Debonding: The contact lens blank is separated from the male mold to obtain the contact lens.

6. The method for preparing a contact lens according to claim 5, characterized in that: In step (1), the stirring speed is 100-200 r / min and the time is 4-5 h.

7. The method for preparing a contact lens according to claim 5, characterized in that: In step (3), the specific operation steps of the pattern printing are: first, the designed contact lens pattern is engraved on the steel plate, then printed on the convex mold by a pad printing machine, and finally the convex mold is placed in a 100-120°C blast oven for drying for 100-150 minutes to obtain a convex mold printed with a color pattern.

8. The method for preparing a contact lens according to claim 5, characterized in that: In step (4), the oven is charged with 99.999% nitrogen, and the oven drying temperature is set to 110-120° C. for 40-60 minutes.

9. The method for preparing a contact lens according to claim 5, characterized in that: In step (5), the specific operation steps of demoulding are: the male mold pressed together after drying is separated from the female mold by a separator, and the contact lens blank is adhered to the male mold, and the male mold containing the contact lens blank is obtained after separation.

10. The method for preparing a contact lens according to claim 5, characterized in that: In step (6), the specific operation steps of the stripping are: separating the contact lens blank from the male mold by a separator, and the contact lens blank after separation is a contact lens with optical power.